(untitled) (Transmediterranean History, 2019)
In the acts of the Seventeenth Council of Toledo (694), the Jews of the Visigothic realm were accused of having conspired against the king and the Christian order along with their North African co-religionists. Their punishment was dispossession and enslavement. The article investigates the living conditions of Visigothic Jews in the seventh century. These are considered both in the broader context of anti-Jewish measures in the wider Mediterranean and against the backdrop of the Muslim advance in North Africa.